THE EFFECT OF BRAND IMAGE AND TASTE ON IMPULSE BUYING OF THAI TEA PRODUCTS - Wan Fitriana Meli; Raihanah Daulay (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the influence ofbrand image and taste on impulse buying thai tea products in students of the University of Muhammadiyah North Sumatra. The problem in this study is whether the brand image and taste affect the impulse buying of Thai tea products in students of the University of Muhammadiyah North Sumatra. The population of this study was limited to Students of the Faculty of Economics and Business who had already purchased thai tea products, the sample of this study was 97 respondents. Data collection techniques use documentation studies, interviews and questionnaires that are tested for validity and reliability. Data analysis techniques use multiple linear regression, classical assumption test, t test, F test and coefficient of determination.The results of the study found that partially brand image has an effect but not significantly on impulse buying, partially taste has a significant effect on impuse buying and simultaneously brand image and taste have a significant effect on impulse buying thai tea products in Students of Muhammdiyah University of North Sumatra.